Psychological distress and adaptation to the COVID-19 crisis in the United States - Daly, Michael; Robinson, Eric (Journal of psychiatric research, 2021)
There is growing concern that the COVID-19 crisis may have long-standing mental health effects across society particularly amongst those with pre-existing mental health conditions. In this observational population-based study, we examined how psychological distress changed following the emergence of the COVID-19 crisis in the United States and tested whether certain population subgroups were vulnerable to persistent distress during the crisis. We analyzed longitudinal nationally representative data from eight waves of the Understanding America Study (UAS) collected between March 10th and July 20th, 2020 (N = 7319 Observations = 46,145). Differences in distress trends were examined by age, sex, race/ethnicity, and household income and by the presence of a pre-existing mental health diagnosis. Psychological distress was assessed using the standardized total score on the Patient Health Questionnaire-4 (PHQ-4). On average psychological distress increased significantly by 0.27 standard deviations (95% CI [0.23,0.31], p < .001) from March 10–18 to April 1–14, 2020 as the COVID-19 crisis emerged and lockdown restrictions began in the US. Distress levels subsequently declined to mid-March levels by June 2020 (d = –0.31, 95% CI [–0.34, –0.27], p < .001). Across the sociodemographic groups examined and those with pre-existing mental health conditions we observed a sharp rise in distress followed by a recovery to baseline distress levels. This study identified substantial increases in distress in the US during the emergence of the COVID-19 crisis that largely diminished in the weeks that followed and suggests that population level resilience in mental health may be occurring in response to the pandemic. •The global spread of COVID-19 may have had an enduring impact on mental health.•Longitudinal nationally representative studies addressing this topic are scarce.•This study examines mental health beyond the initial stage of the COVID-19 crisis.•Identifies a substantial rise in distress in the U.S. from March to April 2020.•Psychological distress levels returned to baseline by June 2020.